The Effect of Capital Expenditure, Cash Conversion Cycle, and Leverage on Financial Performance with Firm Value as a Moderating Variable (A Case Study on Healthcare Sector Companies in 2020–2024) - Prakasa, Arya; Limajatini, Limajatini (LPPM Universitas Buddhi Dharma, 2025)
This study aims to determine the effect of Capital Expenditure, Cash Conversion Cycle, and Leverage as independent variables on Financial Performance as the dependent variable, with Firm Value as a moderating variable. The population in this study consists of healthcare sector companies listed on the Indonesia Stock Exchange during the period 2020–2024, The type of data used in this study is quantitative data sourced from annual financial reports or from annual reports. The sampling technique used in this study is purposive sampling, the data source in this study is secondary data. With a total population of 37 companies in the health sector and a selected sample of 20 companies observed over a 5-year period, resulting in a total of 100 observations. This study employs SmartPLS version 3.2.9 for data analysis. The results of the study indicate that Capital Expenditure has no significant effect on Financial Performance, Cash Conversion Cycle has no significant effect on Financial Performance, Leverage has a significant effect on Financial Performance, Firm Value moderates the relationship between Capital Expenditure and Financial Performance, Firm Value does not moderate the relationship between Cash Conversion Cycle and Financial Performance, and Firm Value moderates the relationship between Leverage and Financial Performance.